Controlled Open Economies A Neoclassical Approach To Structuralisam - Bevan Etal, David (David Bevan Etc, 1990)
Many developing countries are subject to periodic, powerful trade shocks. Unless offset by policy changes, shocks can make the control regime incompatible. The authors of this macroeconomic study analyze the changes needed to maintain compatibility and the consequences of failing to do so.
Keywords: DEVELOPING COUNTRIES-ECONOMIC POLICY; NEOCLASSICAL SCHOOL OF ECONOMICS